Tribe and State: Paradigms of Progress and Development - Shunnaq, Mohammed; Arce, Recardo Sanmartin; Maestro, Juan Ignacio Castien (Journal of Posthumanism, 2025)
In the Middle East, the relationship between tribes and the states has been long and complex, including the tribal system in many states, Jordan included. The modernization efforts of the state had impacted tribal traditions but continued to influence and even determine political loyalties and the social identity of the citizens. Jordan’s political and social framework is constituted mainly by tribes. Historically, tribal leaders were very important in Jordan’s system of governance, and today, more than ever, are quite integrated into modern Jordanian politics. The study aims to examine Jordan’s political evolution through the tribal heritage that exists within its constitutional monarchy and democratic system. The study uses qualitative analysis of historical and contemporary material, such as sources of information on tribal governance and political influence in Jordan. Results indicate that even with modernization, tribes have a strong influence on the political process in Jordan and are a continuing force in governance. In conclusion, the integration of tribal customs into the modern Jordanian state has occurred. However, the on-going interaction between state and tribal organizations is central to the political stability and identity of Jordan.